Sequential allogeneic transplantation and ruxolitinib maintenance for a synchronous PCM1‐JAK2 positive myeloid sarcoma and acute B‐lymphoblastic leukemia. Issue 1 (7th January 2022) - Rizzuto, Giuliana; Leoncin, Matteo; Imbergamo, Silvia; Taurino, Daniela; Mico, Maria Caterina; Tosi, Manuela; Michelato, Anna; Buklijas, Ksenija; Spinelli, Orietta; Lussana, Federico; Lessi, Federica; Pizzi, Marco; et al.
Abstract: The translocation t(8;9)(p22;p24) results in the production of a chimeric PCM1 ‐ JAK2 fusion protein leading to the constitutive activation of the Janus Kinase 2 that renders this disease potentially sensitive to ruxolitinib. Here, we report an interesting case of PCM1 ‐ JAK2 myeloproliferative neoplasm evolving in myeloid sarcoma and B precursor ALL. Abstract : The identification of a specific molecular marker offered the possibility to monitor the depth of remission after transplant and to start an early preemptive therapy with ruxolitinib as soon as any evidence of disease reappraisal was documented.